2016
DOI: 10.1016/j.redox.2016.08.009
|View full text |Cite
|
Sign up to set email alerts
|

The pulmonary inflammatory response to multiwalled carbon nanotubes is influenced by gender and glutathione synthesis

Abstract: Inhalation of multiwalled carbon nanotubes (MWCNTs) during their manufacture or incorporation into various commercial products may cause lung inflammation, fibrosis, and oxidative stress in exposed workers. Some workers may be more susceptible to these effects because of differences in their ability to synthesize the major antioxidant and immune system modulator glutathione (GSH). Accordingly, in this study we examined the influence of GSH synthesis and gender on MWCNT-induced lung inflammation in C57BL/6 mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 61 publications
1
8
0
Order By: Relevance
“…Both studies showed that N-doped exposure increased cellularity and neutrophilia compared to the Vehicle instillation. This type of cellularity/neutrophilia has also been demonstrated with MWCNT exposure in mice [32] and rats [33]. One contrast between our two studies were that CD-1 mice did not present with increased BALF protein concentration after N-doped exposure, as was seen with the C57BL/6 mice [5].…”
Section: Discussionsupporting
confidence: 46%
“…Both studies showed that N-doped exposure increased cellularity and neutrophilia compared to the Vehicle instillation. This type of cellularity/neutrophilia has also been demonstrated with MWCNT exposure in mice [32] and rats [33]. One contrast between our two studies were that CD-1 mice did not present with increased BALF protein concentration after N-doped exposure, as was seen with the C57BL/6 mice [5].…”
Section: Discussionsupporting
confidence: 46%
“…Further, CNTs reduced the expression of CD69 (marker of NK cell activation), CD107a, NK1.1, TNF‐α, IFN‐γ, and reduced the cytotoxicity of NK cells . In some contexts, however, CNTs have been found to be potently inflammatory (e.g., generating pulmonary inflammation and fibrosis via inhalation) . When cultured on sheets of CNTs, dendritic cells were less capable of inducing T cell proliferation or performing pinocytosis, produced less IL‐6 and IL‐10, downregulated CD80, and yet increased secretion of TNF‐α .…”
Section: Immunomodulatory Materialsmentioning
confidence: 99%
“…Therefore, strain susceptibility to pulmonary fibrosis may depend on the agent used to induce fibrosis. Of interest, the sex of mice has also been linked to the inflammatory response experienced by mice following MWCNT aspiration exposure where female mice, especially those with reduced glutathione levels, have reduced neutrophilia and MWCNT clearance from their lungs 110 . Currently, there is a lack of information on sex differences in response to pulmonary exposure to CNTs.…”
Section: Genetic Susceptibility To Pulmonary Fibrosismentioning
confidence: 99%